Evaluation of expelled soybean meal in starter diets - C G Mills; K G Friesen; Robert D Goodband; Michael D Tokach; Jim L Nelssen (1991)
Forty-eight weanling pigs (6.9 lb initial wt) were used in a 28-d growth study to determine the feeding value of expelled soybean meal (43% CP) as compared to conventionally extracted soybean meal (48.5% CP). Pigs were fed one of two dietary treatments containing either expelled soybean meal or conventional soybean meal. Both diets contained milo and 10% dried whey and were formulated to be slightly lysine deficient (.95%) to determine any potential differences in amino acid availabilities between the two soybean meals. From d 0 to 14, pigs fed conventional soybean meal had higher average daily gain (ADG) and average daily feed intake (ADFI) and were more efficient (F/G; 26.2%, 11.3%, and 21.6%, respectively) than pigs fed expelled soybean meal. Similar trends were noted for the overall experiment (d 0 to 28)